Implementasi Program Pengabdian Masyarakat : Penanaman Bibit Dan Peningkatan Penerangan Jalan Di Desa Sasak Panjang Kabupaten Bogor - Poernomoputri , Tyara Pratiwi; Asri, Tika Kartika; Wuryanto, Jarot (CV. ITTC INDONESIA, 2026)
A community service program through fruit seedling planting and street lighting activities in Sasak Panjang Village, Tajur Halang District, Bogor Regency aims to improve environmental quality and community comfort. The implementation method is participatory through field surveys and outreach. The results of the activity show an increase in community awareness of the environment, improvements in the aesthetics of public spaces, and increased security and comfort for residents. Key success factors are high community participation and support from the Sasak Panjang Village Head and her staff. This program is a model of community service that integrates ecological and social aspects.